Low frequency tapping systems applied to young-tapped trees of Hevea brasiliensis (Willd. ex A. Juss.) Müll. Arg. in Southern Thailand - Sainoi, Thongchai; Sdoodee, Sayan; Lacote, Regis; Gohet, Eric (Agriculture and Natural Resources, 2017)
A declining rubber price and labor shortages in the context of climate variability are problems for rubber smallholders. A low frequency tapping system that may be a solution to these problems was tested in southern Thailand using eight-year-old trees of the RRIM600 clone at the Thepa Research Station, Songkhla province. The experimental design was a randomized complete block with five treatments defined in Table 1 and abbreviated to: T1: S/3 d1 2d/3; T2: S/2 d2; T3: S/2 d3 ET 2.5% Pa1 (1) 8/y (m); T4: S/3 d2 ET 2.5% Pa1 (1) 4/y (m); and T5: S/3 d3 ET 2.5% Pa1 (1) 12/y (m). There were three replications (elementary plot) with 10 trees per treatment in each elementary plot. The results showed that low frequency tapping systems (d3) with stimulation resulted in an equivalent yield in cumulative latex production compared with the other tapping systems and also had higher latex production per tapping. Bark consumption was less in the low frequency tapping systems leading to the possibility of lengthening the economic lifespan of the tapping panels of the tree. A low frequency tapping treatment with stimulation eight times per year induced decreases in the total solids, sucrose and reduced thiol contents; however, the inorganic phosphorus content increased, as is usually seen with the use of ethylene stimulation. The response of rubber trees to a low frequency tapping system should now be tested in the long term.